Persistence of jump-induced tail risk and limits to arbitrage. Issue 4 (3rd April 2023) - Chow, K. Victor; John, Kose; Li, Jingrui; Sopranzetti, Ben
Abstract : We present a novel methodology to calculate the jump-induced tail risk premium for individual stocks and examine its effect on the following-month's returns. The existence of a premium for bearing negative jump-induced tail risk is significantly associated with negative one-month future returns. In contrast, the existence of a positive premium for bearing jump-induced tail risk has no such significant predictive power. Further, we find that the larger is the magnitude of the premium for negative jump-induced tail risk, the greater and longer-lasting is its impact on expected returns. Lastly, the observed ten-day lag taken to fully incorporate negative jump tail information into price is consistent with limits to arbitrage in the underlying stocks.